The Muppet show. Season two [videorecording (DVD)] - Henson, Jim; Oz, Frank (Distributed by Buena Vista Home Entertainment, 2007)
A musical-variety program with a cast made up of Muppets and guest stars. So, go bonkers with Beaker, goofy with Gonzo and join the brave cast of "Pigs in space" for Muppet fun.